Setting the Readiness of Law to Implement Central Bank Digital Currency in Indonesia - Suwardiyati, Rumi; Ahmad, Azlin Alisa; Reka Dewantara; Dwi Benny Satria; Ranitya Ganindha (Arena Hukum, 2024)
The shift in behaviour from conventional to technology-based patterns has led to technological transformation, giving rise to an emerging digital currency: crypto. Crypto assets have great potential to develop financial system inclusion and efficiency while it can pose various risks affecting economic, monetary and financial system stability. The Indonesian government's strategic step to curb the use of cryptocurrencies is to issue Central Bank Digital Currency (CBDC). To date, 109 countries have begun to adopt the use of CBDC. The adoption of CBDC in Indonesia has not yet reached the implementation stage, but is still at the research stage. In line with this, this research aims to examine the readiness of Indonesian law to welcome the enactment of CBDC and to prepare an ideal legal construction in regulating CBDC in Indonesia. This paper employs a normative juridical research method with statutory and comparative approaches. The statutory approach involves examining the norms relating to CBDC, while the comparative approach aims to compare the norms applicable in China and the Bahamas regarding the use of CBDC. The results of this study reveal that the Indonesian government's legal readiness to implement CBDC will begin to enter the experimental stage after the P2SK Law recognises CBDC as a legal payment instrument and BI as the authority authorised to manage CBDC in Indonesia. The results of the comparison with China and the Bahamas show that the determination of the CBDC distribution model and the technology used is an important aspect that needs to be considered in preparing the ideal legal construction because it relates to the technological access capabilities of the community to use CBDC.